Syngas Production from Pyrolysis of Nine Composts Obtained from Nonhybrid and Hybrid Perennial Grasses - Adéla Hlavsová; Agnieszka Corsaro; Helena Raclavská; Dagmar Juchelková; Hana Škrobánková; Jan Frydrych (The Scientific World Journal)
A pyrolysis of compost for the production of syngas with an explicit H2/CO = 2 or H2/CO = 3 was investigated in this study. The composts were obtained from nonhybrid (perennial) grasses (NHG) and hybrid (perennial) grasses (HG). Discrepancies in H2 evolution profiles were found between NHG and HG composts. In addition, positive correlations for NHG composts were obtained between (i) H2 yield and lignin content, (ii) H2 yield and potassium content, and (iii) CO yield and cellulose content. All composts resulted in H2/CO = 2 and five of the nine composts resulted in H2/CO = 3. Exceptionally large higher heating values (HHVs) of pyrolysis gas, very close to HHVs of feedstock, were obtained for composts made from mountain brome (MB, 16.23 MJ/kg), hybrid Becva (FB, 16.45 MJ/kg), and tall fescue (TF, 17.43 MJ/kg). The MB and FB composts resulted in the highest syngas formation with H2/CO = 2, whereas TF compost resulted in the highest syngas formation with H2/CO = 3.